PERAN SIMBIOTIK BUDAYA DALAM MEMBENTUK PRAKTIK PENDIDIKAN YANG INKLUSIF - Ismayanti; Nurhayati; Suci Nur Amanah; Hasruddin Nur (STKIP Subang, 2025)
Inclusive education emphasizes equal access, participation, and respect for student diversity, including social, cultural, linguistic, and other background differences. In multicultural societies, culture plays a strategic role in shaping inclusive educational practices. This article aims to analyze the symbiotic role of culture in fostering inclusive education by examining the relationship between cultural values, learning strategies, and the development of inclusive learning environments. This study employs a qualitative approach using a literature review method, drawing on relevant national and international scholarly sources. The findings indicate that culture serves as a fundamental value base for inclusive education and maintains a symbiotic relationship with educational practices, in which education adapts to students’ cultural contexts while also transforming cultural values. The integration of local cultural values into curricula and learning processes enhances students’ motivation, participation, and character development. However, the implementation of culture-based inclusive education still faces challenges, such as the dominance of majority cultures, limited teacher competence, and insufficient policy support. Keywords: inclusive education, culture, cultural symbiosis, diversity